TINJAUAN YURIDIS TERHADAP PENGAKUAN TAIWAN SEBAGAI NEGARA MENURUT HUKUM INTERNASIONAL: Juridical Review Of Taiwan's Recognition As A State Under International Law - Muhammad Farrel Abinoza; Diny Luthfah (Faculty of Law, Universitas Trisakti, 2025)
The Montevideo Convention of 1933 does not explain in detail how a state that lacks recognition from other countries can become a state, whether a state that lacks recognition can become a state, in the context of this study whether Taiwan is a state according to International Law and what is the status of the state of Taiwan (ROC) after the issuance of United Nations General Assembly Resolution 2758 on the Restoration of the legitimate rights of the People's Republic of China at the United Nations. The type of research used in this study is normative towards the recognition of Taiwan as a state according to international law, as stated in the Montevideo Convention on the Rights and Duties of States in 1933. The nature of this research is descriptive analytical, which is research that aims to describe situations, personal behaviour, or group behaviour that has a relationship between one situation and another by relying on library material. Data processing is done qualitatively, then the conclusion will be made deductively. Based on the above analysis that: Taiwan can be said to be a state based on objective criteria for a state in accordance with the Montevideo Convention of 1933 Article 1 and that Taiwan's lack of recognition due to the issuance of UN Resolution 2758 is not a requirement for the establishment of a state, this is evidenced by the existence of Article 3 of the same convention which states that a state will remain a state even if other countries do not give recognition to the existence of the state.